ANALYSIS OF COMMON STRATEGIES IN THE TRANSLATION OF HISTORICAL TEXTS - Abdullayeva Umida Abdumutal qizi, (TADQIQOTLAR, 2026)
Abstract The  translation  of  historical  texts  presents  unique  challenges  due  to  the complexity of language, culture, and historical context. This article examines the most commonly  used  strategies  in  translating  historical  works,  focusing  on  linguistic, cultural, and stylistic aspects. The study is based on a comparative analysis of selected historical texts and their translations into English, highlighting the ways translators address cultural realia, archaic terminology, and stylistic features. The findings indicate that  strategies  such  as  transliteration,  adaptation,  paraphrasing,  and  explanatory commentary  are  frequently  employed  to  maintain  the  meaning,  authenticity,  and readability  of  the  original  text.  The  study  concludes  that  successful  translation  of historical texts requires a balanced application of these strategies, combining linguistic accuracy with cultural and historical intelligibility.